Comparative Study of Conventional and Partial RCC Beams and Slabs for Flexural and Shear strength – A review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
IS456-2000, Clause 38.1 Assumptions, one of the assumptions is; the tensile strength of concrete is ignored. As per this assumption, Instead of using high grade concrete in tension zone, use of nominal grade concrete or creating vacuum near neutral axis, to develop “Partial RC beam or slab”. Both beam and slab are bending structural elements, hence understanding of flexural and shear strength is very important. Review of research papers gives an insight on difference between conventional and partial bending elements. Ultimate flexural strength will be nearly same in both partial elements and conventional bending elements. Initial crack load is less in partial bending elements compare to conventional elements. But partial elements are the best solution to reduce usage of cement in RC structural elements. Understanding shear strength of partial bending elements is very essential in the shear reinforcement design, but less research work is done on shear strength of partial flexural elements. Use of less cement in partial elements reduces CO2 emission, makes structure economical and it is also the solution for global warming